Moléculas de superfície liberadas pelas formas metacíclicas do Trypanosoma cruzi modulam negativamente a invasão celular - Clemente, Tatiana Mordente [UNIFESP] (2016)
Molecules released by pathogenic microorganisms can modulate the interaction with their hosts. We investigated whether metacyclic trypomastigote (MT) forms of diferent strains of Trypanosoma cruzi differencially released extracelular vesicles and soluble proteins, and examined their effect on MT invasion of host cells, focusing on the surface molecules gp82 and gp90. MTs of highly infective CL strain and poorly infective G strain were incubated for 1 h in complete medium (D10) or in PBS++. Conditioned medium (CM), collected after centrifugation of parasites and designated as CM-G and CM-CL, was used for cell invasion assays and Westen blot analysis. Hela cells were incubated for 1 h with MTs of CL strain in D10, or of G strain in PBS++ that induces the scattering/exocytosis of lysosomes and promotes parasite invasion, in the absence or presence of CM. Parasite internalization was significantly reduced in the presence of CM-G but not of CM-CL. Analysis of CM by Western blot, using monoclonal antibodies against gp82 and gp90, which function as promoter and negative regulator of cell invasion, respectively, revealed high levels of gp82 and gp90 in CM-G and low levels in CM-CL. G strain CM generated in PBS++, containing lower amounts of gp90 e gp82 when compared to CM produced in D10, displayed a lower inhibitory effect on invasion by MTs. Preincubation of CM-G (D10) with anti-gp90 or anti-gp82 antibody that does not recognize live MTs neutralized the cell invasion inhibitory activity. Vesicles of diverse size and soluble factors, obtained by fractionation of CM-G and containing gp82 and gp90 molecules, were capable of significantly inhibiting cell invasion by MTs. Our results suggest that factors spontaneously released by MTs, containing high levels of gp82 and gp90, interfer with parasite internalization, gp82 presumably competing for the host cell receptor with the molecule expressed on MT surface, and gp90 further contributing to down modulate invasion.